Match and mismatch on the German labor market - Wolfgang Franz (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
It is often claimed that growing labor market imperfections and maladjustments can be blamed for the increase and persistence of unemployment in the Federal Republic of Germany. This paper attempts to marshall the empirical importance of these factors. Higher structural unemployment seems to be significantly evidenced by shifts of the Beveridge curve and by results obtained from a macroeconometric disequilibrium model. Possible causes of higher structural unemployment are then examined such as reduced labor mobility, higher regional and qualifications mismatch, increased employer choosiness, lower search intensity, more institutional regulations such as dismissal protection laws, higher unemployment compensation, and the like. It seems safe to say that the probable increased malfunctioning of the labor market does not stem from an accelerated pace of structural change. Moreover, one can guess that some higher imbalances in terms of qualifications and a greater employer choosiness are more promising candidates which have interfered with the smooth equalizing of labor demanded and supplied.
Keywords: 330